Move more at your desk : increase your energy at work & reduce back, shoulder & neck pain - Bradley, Kerrie-Anne (Watkins, 2022)
Outlines simple exercises to counter physical issues caused by sitting still for too long, with movements that can be done easily throughout the day to improve sitting posture, strength, and flexibility.